METHOD OF TEACHING ANTONYMS IN MILITARY SYSTEM - Karimova Gulshod Mamatkadirovna; Tohirova D. J. (Journals Park Publishing, 2023)
Antonyms play a crucial role in developing the verbal skills of military personnel, enabling effective communication, precise understanding, and strategic decision-making. This article explores the significance of teaching antonyms in the military system and presents a comprehensive methodology for incorporating antonym instruction. The article highlights the importance of annotation and keywords, followed by sections on the introductory overview, methods employed, obtained results, a discussion of findings, and concluding remarks with suggestions for future implementation.
Keywords: Antonyms, military system, verbal skills, communication, strategic decision-making.